The Economic Factors of the ‘Abbasid Decline During the Buwayhid Rule in the Fourth/Tenth Century - Udjang Tholib (Al-Jami'ah Research Centre, 2009)
Abbasid caliphate in the fourth/tenth century suffered from a sharp economic decline. This was the result of several factors, mainly civil wars, the Zanj and Qarmatian revolts, political interference by the Turkish and Daylamite soldiers, military iqta‘ and the activity of the ‘ayyarun. The civil wars had a destructive effect on the city of Baghdad and its citizens, ruined most of the land and caused a devaluation of dirham and dinars. The revolts of the Zanj and Qarmatians paralyzed trade in southern Iraq leading to a stagnation of currency and the banking system and a decrease in financial activity. The involvement of the Turkish and Daylamite soldiers in politics, and rivalries among them to gain power, led to the devastation of canals, dams and consequently ruined the agricultural sector. In addition, the introduction of military iqta‘ during this period resulted in the damage of cultivated lands due to their excessive exploitation and abandonment of their irrigation system. Finally, the activities of the ‘ayyarun in looting merchants' goods, burning many houses, and killing people, inflicted considerable loss on the merchants, encouraging the latter to leave Baghdad and do business in other cities.